Genesis of the Concerto for Orchestra - Rakochi, Vadim (Journal of History Culture and Art Research, 2020)
The main goal of this article is to classify the origins of the concerto for orchestra and thus to determine its genesis. The methodologies applied include the analytical (study of literature), the functional (concerto for orchestra in the context of musical culture), and the historical (transformation of the genre due to the evolution of orchestral thinking) approaches. A mainstream tendency for synthesis of different styles within the disappearance of the very concept of ‘normal––un-normal’ regarding the orchestra should be mentioned as the first factor which caused the birth of the concerto for orchestra. No matter how important the changes in the orchestra’s functions and structure along with the fusion of different origins for the genesis of the concerto for orchestra were, it is true that it was not a single factor which influenced the genre transformations of the concerto. Search for new sounds and techniques to embody them, popularity of the chamber orchestra, strengthening and diversifying of the ‘inside-the-orchestra solo’, growth of theatricality in symphonic music, transformation of longstanding genres and amplification of the colorfulness in the orchestra are the principle reasons for the appearance of the concerto for orchestra in 1925. The review of Hindemith’s, Petrassi’s, Bartók, Tippett’s and Lutosławski’s concertos demonstrates two different approaches to the synthesis. The conclusion of this article is that the rethinking of the ‘old’ genres within a tendency to synthesize different styles and to merge dissimilar music schools, folklore and ‘classical’ music in tandem with transformations that stroked the integrity of the orchestra as a whole, paved the way for the birth of the concerto for orchestra. The concerto for orchestra became one of the iconic genres of twentieth-century music and embodied ‘a positive vision of a world in a kind of harmony’ in a number of works.